Intermedial Negative: The Role of Punk Cinema in the Downtown Scene (New York, 1976-1984) - Céline Murillo (Interfaces)
No Wave cinema of the 1970s is caught in several intermedial mechanisms as one realization of the transmedial punk movement. No Wave is anti-everything and refuses many rules just like punk rock does. No Wave films are interested in No Wave music and use it as their score while their style deviates from the norm just like the music does. In addition, these films were created by a “scene” of artists that had flocked to New York to take advantage of the cheap lifestyle. All refused know-how in accordance with punk DIY ethos, hence they did not attach themselves to any art or media. However, cinema occupied a specific place, first because of its inherent complex multifaceted mediality that could have an affinity with the punk movement, but also because its mainstream was the very media that these artists wanted to attack by creating alternative forms of it, since it was the dominant mass-media that carried the hegemonic norms.